Pressurisation leads to better cement penetration into the glenoid bone - Raiss, Patric; Sowa, Boris; Bruckner, Thomas; Eck, Simon; Wörz, Stefan; Rohr, Karl (The bone & joint journal, 2012)
The aim of this study was to compare a third-generation cementing procedure for glenoid components with a new technique for cement pressurisation. In 20 pairs of scapulae, 20 keeled and 20 pegged glenoid components were implanted using either a third-generation cementing technique (group 1) or a new pressuriser (group 2). Cement penetration was measured by three-dimensional (3D) analysis of micro-CT scans. The mean 3D depth of penetration of the cement was significantly greater in group 2 (p < 0.001). The mean thickness of the cement mantle for keeled glenoids was 2.50 mm (2.0 to 3.3) in group 1 and 5.18 mm (4.4 to 6.1) in group 2, and for pegged glenoids it was 1.72 mm (0.9 to 2.3) in group 1 and 5.63 mm (3.6 to 6.4) in group 2. A cement mantle < 2 mm was detected less frequently in group 2 (p < 0.001). Using the cement pressuriser the proportion of cement mantles < 2 mm was significantly reduced compared with the third-generation cementing technique.
Published online: 1 May 2012
Gesehen am 04.10.2018